Pharmacognostical and Phytochemical Study of Ayurveda Formulation Named Gandhakadi Yoga with and without Pippali - Meena, Uganta; Meena, Sudarshan; Kori, V K (International Research Journal of Ayurveda & Yoga, 2022)
Many medicinal plants have been used in Ayurveda whose oneness depends on synonyms and vernacular names. It is difficult for proper identification of all source plants and comparison of the drugs which is described in Ayurvedic literature. But with the help of botany and its divisions it can be possible. One can get proper information about Adulteration, Quality Control, and Substitution of raw drugs with the help of Pharmacognosy. Present study was undertaken in order to confirm the authenticity of the drugs used in the preparation of both Drug A (Gandhakadi yoga with pippali) and Drug B (Gandhakadi yoga without pippali); To analyse the sample of both Drug A and Drug B by utilizing suitable parameters and to distinguish the prepared drugs. The results were compiled and presented in organized manner.